Genes and Quantitative Trait Loci Controlling Biomass Yield and Forage Quality Traits in Perennial Wildrye. Issue 1 (1st January 2014) - Larson, Steven R.; Jensen, Kevin B.; Robins, Joseph G.; Waldron, Blair L.
ABSTRACT: Native perennial grasses have potential as low‐input biomass feedstocks. Basin wildrye [ Leymus cinereus (Scribn. & Merr.) Á. Löve] is the largest native grass in western North America but is susceptible to defoliation. Creeping wildrye [ Leymus triticoides (Buckley) Pilg.] is a shorter less productive grass with durable rhizomes and higher forage quality. Two creeping wildrye pseudo‐backcross populations derived from interspecific hybrids were used to identify quantitative trait loci (QTL) controlling plant height, rhizome spreading, flowering, postanthesis biomass yield, cellulosic fiber, lignin, and protein traits using a linkage map comprising 376 expressed sequence tags and 423 other DNA markers. Biomass yields of the F1 hybrids and pseudo‐backcross populations were significantly greater than creeping wildrye with some genotypes nearly equal to or greater than basin wildrye. Rhizome spreading and forage quality of the creeping wildrye pseudo‐backcross populations were significantly greater than basin wildrye. Six of nine plant height QTL overlap with biomass QTL. Three flowering QTL detected in both populations overlap with fiber QTL. Plant height and flowering QTL were aligned to genes controlling dwarfing, photoperiod response, and vernalization in wheat ( Triticum aestivum L.) and barley ( Hordeum vulgare L.) using the Brachypodium distachyon (L.) P. Beauv. genome reference sequence. Evidence suggests that genetic mechanisms controlling plant height and flowering are conserved among temperate grasses and reveals pathways for improving biomass production and forage quality.